Dialética grega : de Zenão a Aristóteles como um caminho para as práticas de investigação - Venceslau, Rodrigo Antonio Gino (2024)
This dissertation aims to understand, present and address the main concepts of Greek dialectics and its investigative nature as a path to research practices. With Zeno of Eleia, disciple of Parmenides, one of the most famous of the Eleatic school, a school that defended questions of a logical, metaphysical, monistic nature and against the notion of movement. Zeno became famous for at least two reasons, the first for his argumentative technique, the second for leading his opponents' arguments to a paradox. Instead of denying his opponent's position, Zeno began by affirming this position and then, by explaining the thesis, he took it to the point of absurdity and only then refuted it. It is precisely within this perspective that Zeno became one of the first philosophers to have discovered élenchos, that is, the method of refutation as one of the safest ways according to Aristotle to examine a thesis. In Aristotle's writings, dialectics is considered a substitute, an auxiliary of science and philosophy, a type of reasoning, a tool in the production of arguments, works, and the self-production of men. Our interest is to show Greek dialectics as a discipline of technical exercise with rules and theory, which practices refutation as the safest way to test an argument and prove its aptitude. We focus on the fact that she is a servant of science, and as a servant, she does not concern herself with the truth. And, taking into account the inability to reach the truth, this art is satisfied with what is credible (eikos), that is, with what seems likely to be shared by the majority (endoxas) or by the wise. It is one that seeks to remain within the limits between opinion (doxa) and science (episteme). In short, we will show Greek dialectics as a reference to the search for truth, showing that the same problem that goes from the Eleatics to the Hereclatians, from the sophists to Plato and which also comes under the domain of Aristotle, seeks to confront the threat of becoming, and provide a certain stability. Still with Aristotle, we will see, in the end, that it is also impossible to have knowledge in flux, a certain stability is necessary: knowledge is only truly scientific at this price or under this condition.